MINDSET SEBAGAI DASAR PENGEMBANGAN PENDIDIKAN ANAK USIA DINI - Hariyanto Hariyanto; Arif Hariyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
Education development now demands struggle and hard work from all parties, especially in the world or the realm of early childhood education. Not a few education experts then offer formulas to maximize the talents and potential of these early childhoods. Early childhood development has not experienced much differentiation or even resistance. Children's lives at this age have unique characteristics, but simultaneously, they provoke the curiosity of all parties. The conception built from the mindset and attitude patterns of children aged 0-6 years (some say early age is children aged 0-8 years) also has its character. Not a few experts in the current field of psychology have tried to examine the dynamics of this early childhood. They compete with the thesis that providing education in early childhood is a significant period in building human resources. Because this period only comes once and cannot be repeated, early stimulation, one of which is education, is absolutely necessary.